Kedudukan al-Istiṣhāb sebagai Dalil Hukum dan Aktualisasinya dalam Bidang Ibadah - Rahmat Rahmat; Kasman Bakry; Sofyan Nur; Afrizal S. Abubakar (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
This research aims to find out the position of al-Istiṣhāb as a law and its actualization in the field of worship. This research represents a type of library research, specifically a library approach, incorporating historical, normative, juridical, and philosophical perspectives. The study yielded the following results: First, al-Istiṣhāb is a legal proposition whose hujjan is disputed. The majority of ulama view al-Istiṣhāb as absolute proof, both in maintaining existing law (daf'ī) and establishing something that does not yet exist (iṡbāt). Meanwhile, according to muta'akhirin scholars from the Hanafiyah school of thought, al-Istiṣhāb is proof of maintaining something that already exists (daf'ī) and not establishing something that did not exist before. In contrast to the two groups of ulama above, the majority of Hanafi ulama, some of the Shafi'ī school of thought, and ahlu kalam ulama (mutakallimin) are of the opinion that Al-Istiṣhāb is not a hujjah at all. Second, al-Istiṣhāb and its actualization in the field of worship are tied to three important pillars, namely, sure, doubtful, and the existence of a connection between what is believed and what is doubted, which must be fulfilled so that it can be used as a legal reference to determine the legal status of a problem.